The opening up of eastern Europe at 20 - jobs, skills, and "reverse maquiladoras" in Austria and Germany - Dalia Marin (Bruegel, 2010)
There were fears in the European Union that eastern enlargement would lead to major job losses and transfers. More recently, these fears have extended to high-skilled and IT jobs. This paper examines using unique firm-level data if these fears are justified for Austria and Germany. We find that eastern enlargement has led to job losses of less than 0.5 percent of total employment in Germany and of 1.5 percent in Austria. Low-cost jobs in affiliates in eastern Europe help Austrian and German firms stay competitive in an increasingly competitive environment. However, we also find that multinational firms in Austria and Germany are outsourcing skill-intensive activities to eastern Europe, taking advantage of cheap and abundant skilled labour there. This is a response to a human capital scarcity in Austria and Germany, which became particularly severe in the 1990s. We find a reverse pattern of `maquiladoras' (a phenomenon seen in the United States and Mexico) between Austria and Germany and their eastern neighbours. Skilled workers in Austria and Germany are losing out from outsourcing. In both countries, outsourcing contributes 35 percent and 41 percent, respectively, to changes in relative wages for skilled workers in Austria and Germany. To address the skill exodus to eastern Europe, we suggest liberalising the movement of high-skilled workers.
Keywords: 330; Auslandsverlagerung; Auslandsverlagerung; Hochqualifizierte Arbeitskräfte; Internationaler Wettbewerb; Standortwettbewerb; EU-Erweiterung; Beschäftigungseffekt; Deutschland; Österreich; EU-Staaten (Osteuropa); Migrationspolitik; Arbeitsmigration; EU-Staaten